IMPLEMENTASI KEBIJAKAN PARIWISATA PADA DESA WISATA - Angga Pramana; Yelly Zamaya; Ardian Ardian; Afrinald Rizhan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The tourism sector presents the potential of the region to become a tourist attraction that encourages regional economic growth and absorbs enormous human resources. An increase in resources needs to be done so that the area's potential can be enjoyed. The government needs government support through policies issued so that tourism is getting better and can improve the economy of the surrounding community. This research focuses on the policy of the provincial government and the Kampar Regency on tourism development, in this case focusing on the Belimbing Island Hamlet, Kuok Village, Kampar Regency. The results of this study indicate that the implementation of Riau Province Regional Regulations, especially in the Belimbing Island Tourism Village, is quite good. Although the current state of application of laws and regulations is still a bit problematic in the laws and regulations related to the tourism sector